2020
DOI: 10.1007/s42452-020-1959-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting defects occurrence in the construction stage of residential buildings in Gaza Strip

Abstract: The building defects are always of great concern for construction industry as they cause delays before handing over and increase maintenance costs during occupancy of the buildings. Due to the rapid development and population growth in Gaza Strip, many residential buildings and housing projects are being constructed in a short space of time, especially after Gaza war in 2014. Therefore, many errors and defects are expected to arise during the construction stage. The aim of this paper is to identify and rank th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Ahzahar et al (2011) pointed out that the usage of materials during the construction stage expect to determine the behaviour of building defects in the future; thus, construction materials are relevant to building defects. Ahzahar et al (2011) and Tayeh et al (2020) have justified using low-quality materials during construction due to parties who intentionally reduce quality to reduce costs. This study revealed that in some of the buildings, a significant number of defects were due to inappropriate material selection concerning the existing climatic conditions and a change in the material types and specifications during the construction process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ahzahar et al (2011) pointed out that the usage of materials during the construction stage expect to determine the behaviour of building defects in the future; thus, construction materials are relevant to building defects. Ahzahar et al (2011) and Tayeh et al (2020) have justified using low-quality materials during construction due to parties who intentionally reduce quality to reduce costs. This study revealed that in some of the buildings, a significant number of defects were due to inappropriate material selection concerning the existing climatic conditions and a change in the material types and specifications during the construction process.…”
Section: Resultsmentioning
confidence: 99%
“…Yacob et al (2019) focussed on establishing the relationship between factors affecting building defects and a building’s condition. Faqih et al (2020) studied factors affecting the physical condition of the building and Tayeh et al (2020) have focussed on studying the factors influencing the occurrence of defects in the construction stage. Talib et al (2014) conducted a study on factors affecting building maintenance and defects.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the previous studies on the causes of building defects, factors causing defects can largely be divided into DCC stages, as shown in Figure 2 [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. As shown in Figure 2, causes of building defects are design errors, the selection of inappropriate materials and methods, no consideration of constructability, and insufficient design documents, etc.…”
Section: Causes Of Building Defectsmentioning
confidence: 99%
“…As shown in Figure 2, causes of building defects are design errors, the selection of inappropriate materials and methods, no consideration of constructability, and insufficient design documents, etc. [34][35][36][37][38][39][40].…”
Section: Causes Of Building Defectsmentioning
confidence: 99%